INTEGRAL STIFFNESS OF THE ARTERIAL SYSTEM AND ENDOTHELIAL FUNCTION IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Yu. E. Teregulov; D. K. Khusainova; D. I. Abdulganieva; F. N. Mukhametshina; M. M. Mangusheva (Научно-практическая ревматология, 2015)
Objective: to study the integral stiffness of the arterial system in patients with systemic lupus erythematosus (SLE) and its relationship to vasoactive regulatory endothelial function.Subjects and methods. The investigation included 51 patients with SLE, including 45 (88%) women and 6 (12%) men at the age of 17 to 52 years (mean age 34±8.3 years). A control group consisted of 31 healthy volunteers aged 22 to 47 years (mean age 31±5.65 years). Among them, there were 23 (74%) women and 8 (26%) men. The ultrasound method described by D. Celermajer et al. and modified by the authors of this article was used to evaluate endothelial function. The cardiovascular system model developed by A.E. Teregulov was employed to calculate volumetric elasticity coefficient (VEC), mean blood pressure (BP), total peripheral vascular resistance (TPVR), and VEC/TPVR ratio. Results and discussion. In the patients with SLE, the stiffness of the arterial system was significantly higher than that in the control subjects (p < 0.001). According to the results of a reactive hyperemia test, the patients with SLE were divided into two subgroups: 1) 20 (39%) patients with a normal response of the brachial artery; 2) 31 (61%) patients with endothelial dysfunction. The values of arterial system stiffness and TPVR were independent of endothelial function,  SLE activity, and kidney involvement. Patients with disease duration more than 5 years had higher VEC (p = 0.049) and VEC/TPVR ratio (p = 0.044) than those with a shorter history of SLE. The stiffness of the arterial system was higher in hypertensive patients (p = 0.049) whereas VEC/TPVR ratios were unrelated to BP values. Thus, as compared with the control subjects, the patients with SLE had significantly higher integral arterial system stiffness that in these patients depended on arterial lesion, disease duration and BP. In SLE patients, endothelial dysfunction did not affect the formation of arterial system stiffness either.